Numerical study on the effectiveness of precursor isolation using N2 as gas barrier in spatial atomic layer deposition. (December 2019) - Pan, Dongqing
Highlights: Bottom purge configuration is more effective in preventing material intermixing than top design in spatial ALD system. Higher N2 injecting flow rate is beneficial to construct an effective gas barrier for precursor isolation. Higher relative purging pressure is more desirable to prevent precursor intermixing. Evenly assigned precursor dosing pressure is advantageous for precursor isolation. Using N2 as gas barrier in spatial ALD system with a large gap is effective for precursor isolation. Abstract: Spatial atomic layer deposition (ALD) is capable to increase film deposition rate dramatically by eliminating the need of traditional pulse/purge steps in ALD process. Numerical simulations offer valuable information on spatial ALD system design and development. In this paper, a numerical study of inline spatial ALD process with a large gap (36 mm) is presented to investigate the effectiveness of precursor isolation using N2 flow as gas barrier in two different geometric designs, namely, top and bottom purge configurations. Bottom purge configuration is shown more effective in preventing precursor intermixing than top design. Higher N2 injecting flow rate and higher relative purging pressure are beneficial to construct an effective gas barrier in spatial ALD system. Evenly assigned precursor dosing pressure is advantageous to further prevent material intermixing. Transient material distributions in the flow field, contour plots of species, velocity field, and material tracelines have confirmed the effective gas barrier built by N2 . Precursor intermixing molar fraction is shown as low as 0.0045%, and the intermixing molar concentration is as low as 9.105 × 10 −5  mol/m 3 . The study provides invaluable information in determining geometric and process parameters for system design, and the effectiveness of precursor isolation using N2 as gas barrier in spatial ALD with a large gap is validated.